2014
DOI: 10.1097/inf.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Rotavirus Diarrhea among Children Younger Than 5 Years in Enugu, South East, Nigeria

Abstract: This study found a relatively high incidence of severe rotavirus-associated diarrhea disease in Nigeria and infants were the most affected. It highlights the urgent need for introduction of rotavirus vaccine into the national immunization program and the need to adequately equip health facilities to enable them administer intravenous fluids to severe diarrhea patients to reduce morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
36
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 19 publications
19
36
6
Order By: Relevance
“…Findings from the current study show that majority of cases occurred between the months of December to April which corresponds to the rotavirus diarrhoeal season as previously reported in a Nigerian study [11].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Findings from the current study show that majority of cases occurred between the months of December to April which corresponds to the rotavirus diarrhoeal season as previously reported in a Nigerian study [11].…”
Section: Discussionsupporting
confidence: 65%
“…Rotavirus is the most common cause of severe dehydrating diarrhoea among infants and young children [11] resulting in about 453,000 mortalities in children <5 years of age annually worldwide (with 232,000 deaths occurring in sub-Saharan Africa) [12] [13].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is comparable to the detection rates reported for African countries where RV vaccine is not yet included in the free national childhood programme: 25.2 % in Egypt (Matson et al, 2010), 18 % in Tanzania (Moyo et al, 2007) and 18 % in Nigeria (Aminu et al, 2010). However, the prevalence of RVA infection in the present study is lower than those found in Morocco (42 %) (Benhafid et al, 2013), Cameroon (42.8 %) (Ndze et al, 2012), southern Ghana (48.2 %) (Enweronu-Laryea et al, 2013), south-eastern Nigeria (56 %) (Tagbo et al, 2014) (Sowmyanarayanan et al, 2012). Such differences may be partly due to the inclusion criteria of each study: differences in the period of study (sampling done during the whole year or focused on only during the outbreak period) and differences in the study populations (children <5 years old versus children <2 years old or sometimes patients of all ages; hospitalized children versus outpatients).…”
Section: Rva Detection Ratecontrasting
confidence: 46%
“…Similar association of type of feed to rotavirus was also reported by John et al, who observed that children on exclusive breast feeds had a reduced prevalence of rotavirus. 22 This was also observed in other studies, where breastfeeding was found to temporarily postpone rather than prevent the outcome. [23][24][25] In contrast, studies from Bangladesh have eported that breast feeding is only a minor contributor to the protection of viral disease.…”
Section: Discussionsupporting
confidence: 69%